A Systematic Review of Acoustic Telemetry as a Tool to Gain Insights Into Marine Turtle Ecology and Aid Their Conservation - Hardin, Emily E.; Fuentes, Mariana M. P. B. (Frontiers in Marine Science, 2021)
While widely applied in fisheries science, acoustic telemetry remains an underutilized method in the field of marine turtle biotelemetry. However, with the ability to provide fine-scale spatial data (tens to hundreds of meters, depending on array setup and receiver range) at a low cost, acoustic telemetry presents an important tool for obtaining key information on marine turtle ecology. We present a comprehensive and systematic review acknowledging how acoustic telemetry has been used to advance the field of marine turtle ecology and conservation. We identify the extent of current studies and discuss common and novel research approaches while addressing specific limitations of acoustic telemetry. Forty-eight studies were reviewed, representing six of the seven marine turtle species and all life stages, with most individuals identified as juveniles (45%) and hatchlings (36%). Most studies (83%) focused on the spatial distribution of marine turtles, including estimating home ranges, investigating drivers of habitat use, and identifying horizontal movement patterns and vertical space use. Additionally, acoustic telemetry has been used to study hatchling dispersal and marine turtle exposure and response to threats, as well as to monitor physiological parameters. We identified that acoustic telemetry directly or indirectly informs 60% of the top questions and research priorities related to marine turtles identified by experts in the field. With an increase in acoustic telemetry receiver networks and collaborations across taxa, the applicability of acoustic telemetry is growing, not only for marine turtles but for a wide array of marine species. Although there are limitations that need to be considered at a site/project-level, acoustic telemetry is an important, low-cost technology able to address key questions related to marine turtle ecology that can aid in their conservation, and therefore should be considered by researchers as they develop their projects.